2009
DOI: 10.1186/1477-7827-7-124
|View full text |Cite
|
Sign up to set email alerts
|

Regulated expression of matrix metalloproteinases, inflammatory mediators, and endometrial matrix remodeling by 17beta-estradiol in the immature rat uterus

Abstract: Background: Administration of a single physiological dose of 17beta-estradiol (E2:40 microg/kg) to the ovariectomized immature rat rapidly induces uterine growth and remodeling. The response is characterized by changes in endometrial stromal architecture during an inflammatory-like response that likely involves activated matrix-metalloproteinases (MMPs). While estrogen is known as an inducer of endometrial growth, its role in specific expression of MMP family members in vivo is poorly characterized. E2-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
22
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 59 publications
6
22
0
Order By: Relevance
“…In agreement with previous studies, we found that estrogen supplementation prevented the downregulation of MMP-2 in the acute and chronic stages of LV remodeling (8,61). Similar estrogenic effects on MMP-2 expression were found in the ventricle and arteries of ovariectomized rats (27,61,64), rat uterus (48), and in cell culture studies (9,18). Estrogen also has a direct regulatory effect on MMP-2 expression in cardiac fibroblasts and vascular smooth muscle cells (18,34,53).…”
Section: Discussionsupporting
confidence: 79%
“…In agreement with previous studies, we found that estrogen supplementation prevented the downregulation of MMP-2 in the acute and chronic stages of LV remodeling (8,61). Similar estrogenic effects on MMP-2 expression were found in the ventricle and arteries of ovariectomized rats (27,61,64), rat uterus (48), and in cell culture studies (9,18). Estrogen also has a direct regulatory effect on MMP-2 expression in cardiac fibroblasts and vascular smooth muscle cells (18,34,53).…”
Section: Discussionsupporting
confidence: 79%
“…KEGG analysis demonstrated that MMP9, CDC42 and IL8 were enriched in more than one pathway, which indicates that these genes serve as the pitch points of these pathways and are crucial for the formation of sexual differences in GBS. MMP9 directly induces the destruction of the extracellular matrix, participates in processes related to leukocyte migration, tumour cells migration, pathogenic E. coli infection, and is related to the deterioration of patients with GBS [5,[7][8][9]. CDC42 can mediate its effects through protein kinase A (PKA), regulate the intracellular activity of focal adhesions and up-regulate the expression of MMP9; as a result, this gene is considered a key factor regulating the interaction between cells and the extracellular matrix [23].…”
Section: Genome-wide Expression Differences Between Male and Female Gmentioning
confidence: 99%
“…Matrix metalloproteinases (MMPs) and tumour necrosis factor (TNF) are highly involved in the demyelinating process of GBS and are associated with disease severity and electrophysiological changes in GBS patients [5,[7][8][9]. MMP9 is highly associated with the transmigration process of inflammatory cells and the degradation of the blood-nerve barrier, while TNF-alpha is related to a cascade of events leading to immune-mediated demyelination and axonal damage, which constitute the two main pathophysiologic processes of GBS [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…It may be worthwhile to mention that estrogen is linked with neoplastic processes of different sites such as the breast, ovary, and endometrium [11][12][13]. Never theless, a growing body of evidence suggests a close association between estrogen and various MMPs, which cleave and remodel the ECM and thereby play a crucial role in tumor progression [14][15][16]. In breast cancer, estrogen was found to modulate tumor MMP-2, MMP-9, and tissue inhibitor of metalloproteinase-1 (TIMP-1) [17,18].…”
Section: Introductionmentioning
confidence: 99%